Subaltern Praxis: A Vygotskian and Freirean Framework in NGO Education - Keyl, Shireen (International Journal of Multicultural Education, 2021)
This article examines the functionality and ideological underpinnings of an NGO system in Beirut, Lebanon. This grassroots NGO, in partnership with the Migrant Community Center and migrant domestic workers from African and Southeast Asian countries, creates an educational space that is both transformative and libratory. This activist space is informed by an anti-racist and feminist ideology. Based on the narratives of this system’s stakeholders, I forward a subaltern praxis, a transformative model for the development sector informed by Vygotsky’s constructivist frameworks and Freirean ideology.